Biosorption of methylene blue and malachite green from single and binary solutions by Pinus pinaster bark - Litefti, Khaoula; Freire, M. Sonia; Stitou, Mostafa; González-Álvarez, Julia (Maderas. Ciencia y Tecnología, 2023)
Aiming to develop a sustainable separation process reducing the water pollution, in this work Pinus pinaster (cluster pine) bark from a wood veneer industry was used for methylene blue and malachite green removal from aqueous systems. For single adsorption, the influence of time (up 8 h), adsorbent dose (2,5 - 5- 10 g·L-1), temperature (25 ºC - 40 ºC - 60 ºC), pH (2 - 4 - 6) and particle size (0,1 mm - 0,5 mm, 0,5 mm - 1 mm and 1,6 mm - 2 mm) on adsorption was investigated. To study the initial concentration effect on binary adsorption, different concentrations (0 - 5 - 25 - 50 mg·L-1) were used at 25 ºC, natural pH and a dose of 5 g·L-1. High efficiency was obtained at pH = 4 (natural pH), dose of 5 g·L-1 and particle size of 0,5 - 1 mm. Adsorption percentages higher than 70 % were reached in less than one hour, with removal almost complete at equilibrium in single systems, without temperature influence. Methylene blue was slightly better adsorbed b ybark. In binary systems, dyes exhibited competitive adsorption, decreasing their removal, especially increasing the ini- tial concentration of the other dye. Dyes adsorption followed the pseudo-second order kinetic model, whereas the Langmuir isotherm explained adsorption equilibria in mono-component systems. High adsorption capac- ities (41,7 mg·g-1 for malachite green and 50,0 mg·g-1 for methylene blue) were obtained at 40 ºC and natural pH indicating that pine bark can be effectively used as biosorbent.